2016
DOI: 10.4103/1305-7456.195177
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of fiber-reinforced composite crowns in pulp-treated primary molars: 12-month results

Abstract: Objective:The aim of this study was to evaluate the clinical performance of tooth-colored fiber-reinforced composite (FRC) crowns in pulp-treated second primary mandibular teeth.Materials and Methods:This split-mouth randomized, clinical trial performed on 67 children between 3 and 6 years with two primary mandibular second molars requiring pulp treatment. After pulp therapy, the teeth were randomly assigned to stainless steel crown (SSC) or FRC crown groups. Modified United States Public Health Service criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
4
1
Order By: Relevance
“…This finding was not following the manufacturer's claims that Fiberglass crown showed higher fracture resistance scores than SSCs. 15 The present results were also inconsistent with Mohammad et al, (16) who compared Fiberglass crown and stainless-steel crowns on primary molars; only one Fiberglass crown out of 67 showed fracture compared to none in the stainless-steel crowns after a follow-up period of 12 months. On the other hand, Mohammad et al .…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…This finding was not following the manufacturer's claims that Fiberglass crown showed higher fracture resistance scores than SSCs. 15 The present results were also inconsistent with Mohammad et al, (16) who compared Fiberglass crown and stainless-steel crowns on primary molars; only one Fiberglass crown out of 67 showed fracture compared to none in the stainless-steel crowns after a follow-up period of 12 months. On the other hand, Mohammad et al .…”
Section: Discussioncontrasting
confidence: 80%
“…On the other hand, Mohammad et al . (16) used a custom-made Fiberglass crown, and tooth preparation demanded removing all undercuts from all surfaces, which allowed for more bulk of the material. Thus, it can be assumed that Fiberglass crown thickness may not be enough to provide a strong material that withstands the forces of mastication.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings were in accordance with other studies that showed high wear behaviour of fiberglass crowns compared to other crown types: Ohlmann B, et al [15] evaluated the clinical wear behaviour of posterior, metal-free polymer crowns, with and without a glass-fiber framework, and compared it with that of metal-ceramic crowns, within a 12-month observation period they found that the mean total wear of posterior polymer crowns with and without a glass-fiber framework was significantly greater than metal-ceramic crowns. Moreover, Mohammadzadeh et al [16] compared the clinical performance of costumed made fiberglass crowns and SSCs in primary molars, they concluded that the SSCs showed significantly higher durability 100%, compared to only 89.7% FRCs at the end of the 1-year assessment. In another clinical study done by Behr.…”
Section: Discussionmentioning
confidence: 99%
“…In 2007, Bernardo et al (Bernardo et al 2007) reported that 94.4% of all amalgam restorations survived for seven years when placed in permanent posterior molars of children aged 8-12. However, amalgam is still the most durable and cost-effective restorative material, but in preschool children with large proximal carious lesions, preformed metal crowns are preferred to amalgam because of their durability (Mohammadzadeh et al 2016).…”
Section: Introductionmentioning
confidence: 99%